Empirical analysis on the impact of monetary policy on the growth of Kenya’s manufacturing sector - Mburu, Byron Gichuhi (Strathmore University, 2017)
The purpose of this study was to find out the impact of monetary policy in boosting manufacturing sector growth in Kenya. This paper uses the Vector Autoregression (VAR) Model to measure the impact of monetary policy on the growth of Kenya's manufacturing sector through analysis of four variables; interest rates which are used as the proxy for monetary policy, exchange rates, real GDP and manufacturing sector GDP. Quarterly time series data was used was for the period 1980-2015. The study finds a significant positive relationship between monetary policy and growth of Kenya's manufacturing sector in the short-run and long-run. Analysis shows that Kenyan exchange rates and lending rates are insignificant as they do not cause a major difference in the manufacturing sector mainly due to fiscal dominance and also due to deregulation in Kenya's financial sector and this is evidenced by figures obtained after running the VAR model. On the other hand, real GDP has significant and positive effect on the growth of Kenya's manufacturing sector. However, when an impulse response function is carried out on the variables, exchange rates are observed to have a positive impact on the growth of the manufacturing sector while interest rates have a negative effect on the growth of the manufacturing sector. In conclusion, stringent policies and information asymmetry need to be put in place when accessing credit facility in favour of firms in the manufacturing sector.
A Research project submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Actuarial Science at Strathmore University
Keywords: Monetary policy; Manufacturing sector; GDP; Interest rates; Vector Autoregression (VAR)